The singularity that cares as a concept tool in the art of midwifery: narratives of traditional midwives (Research, Society and Development, 2021)
Objective: to present actions and arrangements of traditional midwives in the conformation of care in an Amazon region, using their narratives about the context of midwifery as a common thread. Method: Qualitative descriptive research developed through interviewing 15 traditional midwives between 2015 and 2016 and a field journal to support registering the information collected. The construction of the narratives had Walter Benjamin as a theoretical and methodological basis. Results: the narratives express affectivity and construction of subjectivity between midwives and parturients, the affirmation of knowledge produced among women, the natural relationship with the pregnant body and the construction of autonomy, care and support to the person who is parturient. Conclusion: singularity is a concept that is a tool in the art of midwifery that points to the non-objectification of bodies, to the displacements that go through the territory of affections, to the relationships built between midwife and parturient woman and to the construction of subjectivity and autonomy in the ways of walking through life.